Recent technological advances in correlative light and electron microscopy for the comprehensive analysis of neural circuits - Iwasaki, Hirohide; Ichinose, Sotaro; Tajika, Yuki; Murakami, Tohru (Frontiers in Neuroanatomy, 2022)
Light microscopy covers a relatively wide area and is suitable for observing the entire neuronal network. However, the resolution of light microscopy is not sufficient to identify synapses, and it is not clear whether neighboring neurons are connected via synapses. In contrast, the resolution of electron microscopy is sufficiently high to detect synapses and is useful for identifying neuronal connectivity, but serial images cannot easily show the entire morphology of neurons as electron microscopy covers a relatively narrow region. Thus, covering a large area requires a large dataset. Furthermore, the three-dimensional (3D) reconstruction of neurons by electron microscopy requires considerable time and effort, and the segmentation of neurons is laborious. Correlative light and electron microscopy (CLEM) is an approach for correlating images obtained by light and electron microscopy. Because light and electron microscopy are complementary and can compensate for their defects, CLEM is a powerful technique for the comprehensive analysis of neural circuits. In particular, the combination of multi-color live imaging using light microscopy and high-resolution imaging using electron microscopy has contributed to neuroscience and various fields of biological sciences. This review provides an overview of recent advances in CLEM tools and methods. We also discuss the problems and limitations of current CLEM technologies.